The Impact of Legal Traditions on Quebec Procedural Law: Lessons from Quebec’s New Code of Civil Procedure - Jukier, Rosalie (The Canadian Bar Review, 2015)
The adoption of a new Code of Civil Procedure in Quebec provides an opportune moment to consider the reasons for, and consequences of, a new direction in adjectival law. Moreover, it is an appropriate time to reflect on the influence of legal traditions on civil procedure, and the role played by such traditions in the legislative evolution and judicial interpretation of procedural law. This paper analyzes the current trends in civil procedure in Quebec, from both legislative and judicial standpoints, and seeks to relate these trends to tradition-based influences. Ultimately, this study demonstrates that Quebec’s procedural law has experienced great swings of the pendulum – originally inheriting continental civilian procedure from the French, gradually evolving towards a very common law/adversarial notion of procedure, and nowreverting back in a civiliste direction.